2004
DOI: 10.5551/jat.11.79
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Produced by Bone Marrow-derived Cells Attenuates Atherosclerotic Lesion Formation in LDLR-deficient Mice

Abstract: These findings demonstrate that IFN-gamma produced by bone marrow-derived cells delays the progression of atherosclerosis without any effect on plasma lipids, and this suppression may be due to decreased extracellular matrix deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Deficiency in IFN-gR or IFN-g significantly reduces lesion development and enhances plaque collagen content (9, 10), whereas exogenous administration of IFN-g enhances lesion development (10). Surprisingly, one study reported reduced lesion formation in LDLR 2/2 mice transplanted with IFNg-deficient bone marrow (11). The reasons for this discrepancy remain to be elucidated.…”
Section: Th1 Response In Atherosclerosismentioning
confidence: 75%
“…Deficiency in IFN-gR or IFN-g significantly reduces lesion development and enhances plaque collagen content (9, 10), whereas exogenous administration of IFN-g enhances lesion development (10). Surprisingly, one study reported reduced lesion formation in LDLR 2/2 mice transplanted with IFNg-deficient bone marrow (11). The reasons for this discrepancy remain to be elucidated.…”
Section: Th1 Response In Atherosclerosismentioning
confidence: 75%
“…Thus, the current study investigated the possibility that FcgRIIB limits the atherosclerosis development in LDLR-deficient mice. There is abundant evidence that proinflammatory Th1 immune responses against altered self-Ags generated by hypercholesterolemia, such as oxidized LDL particles, have a predominance in atherosclerosis (31,(33)(34)(35)(36)(37). Both innate and acquired proatherogenic immunity is activated by hypercholesterolemia, supporting the concept that the disease at least in part should be considered as an autoimmune disease (5,6).…”
Section: Discussionmentioning
confidence: 88%
“…This technique has been well established to distinguish between the effect of proteins expressed by both smooth muscle cells and hematopoietic cells in the development of atherosclerotic lesions in murine models of atherogenesis. 4,21,22 Indeed, prominent effects of growth factors or cytokines, including MCP-1, 21,22 tumor necrosis factor, 39 and interferon-␥, 40 on hematopoietic elements have been dissected with the use of this technique. Of note, the contribution of monocyte/macrophage recruitment appears early, within 3 to 4 weeks after the start of administration of a high-fat, cholesterol-enriched diet, in lesion development in the ApoE system, with maximal effects noted after 5 to 10 weeks on the high-fat Western diet.…”
Section: Discussionmentioning
confidence: 99%